PENGARUH PERLAKUAN PEMATAHAN DORMANSI TERHADAP VIABILITAS BENIH AREN (Arenga pinnata Merr.) - Manurung, Desy; P. Putri, Lollie Agustina; Bangun, Mbue Kata (Jurnal Agroekoteknologi, 2013)
The objective of this research were to study the influence of dormancy breaking methods onsugar palm seed viability. This research was conducted at screenhouse in Agriculture FacultyUniversity of North Sumatera, Medan (± 25 m asl) from June-September 2012, using completelyrandomized design with 8 treatments (control, water soaking 50ºC, 0.1%KNO 0.5%KNO and 0.1%HCl, 0.2%HCl, 0.3%HCl) with 4 replications. The results showed thadormancy breaking methods were significantly effect to axis embryo length (5 week after planted),germinating time, viability, plant height, diameter bar, numbers root, root length, fresh weight, dryweight and were not significantly to axis embryo length 4 WAP, normal sprout, abnormal sproutand the number  leaf extent.  3Keywords : dormancy, sugar palm. 3,  0.3%KNO3